Protótipo Facilita: a interface digital e a velhice - Viana, Eric Marcel (2017)
The research in your hands traces the way through the definitions of digital native, digital immigrant and technological accent, draws parallels on how technological inequality and intergenerational lag have created groups of people who have different levels of interaction and understanding of contemporary technological instruments and how these levels affect the social interactions of the older people. It also deals with the process of aging and how physical limitations and social problems lead the elderly to distance themselves from digital devices that could bring greater social contact. The text approaches the following definitions of interface, usability, design, technologies and structures that enabled the creation / development of the final product, the digital prototype "Facilita" and closes with new technologies and future points of evolution of the work